Patient profile of gestational trophoblastic disease at Patan Hospital, Nepal - Singh, Alka; Shrestha, Reena (Journal of Patan Academy of Health Sciences, 2015)
Introductions: This study was designed to determine the demographic pattern, incidence, clinical features and management outcome of gestational trophoblastic disease (GTD) in Patan Hospital.Methods: This was a cross sectional study conducted at Patan Hospital from April 13, 2008 to April 12, 2013. Medical record of cases diagnosed as GTD were retrieved from the record section for review. The age, parity, estimated gestational age at the time of evacuation, presence or absence of vaginal bleeding, uterine size in relation to gestational age, ultrasonogram report and urinary beta human chorionic gonadotropin level, histopathology findings, modalities of treatment and outcomes were analyzed.Results: There was total of 41,543 deliveries during five years study period and 54 GTD on histopathology. Among the 54 GTDs, 40 (74%) were molar pregnancy, 8 (14.4%) invasive mole and 6 (11%) choriocarcinoma. The frequency of GTD was 1 per 769 pregnancies. The age of the women with GTD ranged from 15-50 years. Half of the cases were below 25 years. Most of the women presented between 8-12 weeks of gestation and below third gravida. Amenorrhea with vaginal bleeding was seen in 49 (90%) patients.Conclusions: The most common GTD observed in this study was molar pregnancy. Vaginal bleeding was the common complaints at presentation.Journal of Patan Academy of Health Sciences, Vol. 2, No. 1, 2015. page: 3-6